No acute changes in postural control after soccer heading - Broglio, S (BMJ Group, 2004)
Background: Soccer heading has been proposed as a potential cause of cerebral dysfunction. Objective: To examine the acute effects of two types of soccer heading on postural control. Methods: Collegiate soccer players were randomly assigned to one of four groups: control, linear heading, simulated rotational heading, or rotational heading. Each subject completed a baseline postural stability assessment on day 1. On day 2 the same assessment was completed for the control subjects. The simulated rotational heading group completed a simulated heading drill before postural stability testing. The linear and rotational heading groups performed a heading drill with 20 balls at 88.71 km/h (55 mph), before postural stability testing. Separate one between (group), three within (surface, eyes, and day), mixed model, repeated measures analyses of variance were conducted on values for total sway and mean centre of pressure. Results: The mixed model analysis of variance of results showed no significant differences (p>0.05) for the interactions of interest for either variable. Results suggest no acute changes in measures of postural control in soccer players completing either a linear or rotational soccer heading drill of 20 balls at a fixed speed. Conclusion: Non-significant interactions between surface, eyes, day, and group indicate that sensory interaction of the balance mechanism components are not be compromised by the heading drill. This research supports previous studies suggesting that there are no acute risks associated with routine soccer heading. A direct comparison between these findings and those suggesting long term chronic deficits, however, cannot be made. Other studies that report chronic cerebral deficits in soccer players may have resulted from factors other than soccer heading and warrant further examination.